CRITICAL DISCOURSE ANALYSIS INTERPRETING THE FEMINISM MOVEMENT IN INSTAGRAM SOCIAL MEDIA - Tohari, Achmad (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Feminism is often used as an understanding that leads to women who want equality against male domination. This research explains the problem of equality that occurs in social life by focusing on social media instagram as the object of research, the data used in this research is descriptive analytical which includes qualitative research with interview techniques and in-depth observation which is then analyzed using Michel Foucault's Critical Discourse Analysis on informants who are still related to three accounts on instagram. The findings reached that from several feminist accounts on Instagram with twelve correspondents interviewed regarding their understanding of feminist discourse on several accounts, the feminism movement wants to fight social construction in the community by inviting women who are in a position that is always disadvantaged and always discriminated against by men so as to create several discourses on gender equality that continue to be produced by following actual cases on social media by presenting interesting and varied content.